2018
DOI: 10.21608/mjcu.2018.56346
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 17 Expression in Psoriatic Skin Lesions before and after Treatment with Platelet Rich Plasma (PrP)

Abstract: Background: Psoriasis is a chronic immune-mediated inflammatory disorder with epidermal hyperplasia. There is some evidence that the Interleukin (IL) 17 has a role in the pathogenesis of psoriasis. Platelet Rich Plasma (PrP) is autologous concentration of platelets may improve the condition because of its anti-inflammatory nature. Aim of Work: This study has been conducted in an attempt to assess the effect of PrP as a new modality for treatment of chronic localized plaque psoriasis on IL17 expression in psori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…While several clinical studies have demonstrated the effectiveness of PRP therapy in treating plaque psoriasis, their smaller sample sizes have limited the overall understanding of the treatment's impact and the generalization of the results. Although the existing research has shown promising results, the general consensus among medical researchers is that larger, more extensive studies are required [26][27][28][29][30]34]. By increasing the sample size, researchers can establish more substantial evidence of the effectiveness of PRP therapy for plaque psoriasis and further assess the potential benefits and risks associated with the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While several clinical studies have demonstrated the effectiveness of PRP therapy in treating plaque psoriasis, their smaller sample sizes have limited the overall understanding of the treatment's impact and the generalization of the results. Although the existing research has shown promising results, the general consensus among medical researchers is that larger, more extensive studies are required [26][27][28][29][30]34]. By increasing the sample size, researchers can establish more substantial evidence of the effectiveness of PRP therapy for plaque psoriasis and further assess the potential benefits and risks associated with the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One plaque received the intradermal administration of PRP, while the other received normal saline as a placebo. They performed biopsies before and after treatment to investigate the role of IL-17 expression in psoriasis pathogenesis and PRP’s mechanism [ 34 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations